A study on the usage of new media in Malaysia general election 2013 / Ahmad Danish Hairudin and Muhamad Hakimin Mokhtar - Hairudin, Ahmad Danish; Mokhtar, Muhamad Hakimin (Faculty of Administrative Science and Policy Studies, 2013)
Media activist has been banned by Malaysia civil society since before independent, and come back to the networks of progressive journalist and writer to the Malaysia modern nongovernment organization or NGO (Weiss 2003). In Malaysia, they lose three part classification media for information, identity building and mobilization because the impact of the new media. Basically new media are using internet as medium to forward the information. The best examples of the new media are blogs, you tube, face book, twitter, and online news paper. The accessibility towards the media also plays an important role why the new media affects the general election 13 result. People nowadays can access the internet at everywhere and also at anytime they want. The easy accessibility is reasons why more people like to use new media. Internet media was increase because not only for communication but also for extension of the public interest to influence public sphere with the potential to redistribute power for wider range of people and for debate. Thought that it will create a question on how the current generation of new media would change the landscape of politic.